Ketaatan Sistem Pengendalian dalam Organisasi: Kajian Teoretis dan Tinjauan Literatur - Nelfin Kurnia Waruwu; Eri Kusnanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This article presents a theoretical review of organizational control systems with emphasis on adherence to stringent control mechanisms. Through a qualitative literature review approach, this study examines three interconnected control dimensions: result control, action control, and personal-cultural control. The findings indicate that effective organizational control requires an integrative approach that combines formal mechanisms such as performance targets and standard operating procedures with informal aspects including values and organizational culture. Result control provides direction through clear performance indicators, action control ensures work processes comply with established standards, while personal-cultural control strengthens internal compliance through value internalization. This study contributes to management control system theory by emphasizing the importance of integrated control approaches and highlighting the roles of goal communication, value internalization, action tracking, and behavioral reinforcement as key elements in building organizational compliance. Practically, this article offers recommendations for organizational leaders in designing balanced, effective, and sustainable control systems that support organizational goal achievement without undermining employee flexibility and creativity.